(3GdebOeI GdLRhdjIs - (3YjSi Hf YHO GdYRjR Hf jddHNJ GdLRhdj GdHQHQj GdeQGcTj, CHh ehSi,J (B607 (3g` s
(3ChdgG (B:s
(3GdcdGe gh GddaX GdeQcH GdeajO HGdhVY, cd LfS bSe Edi CfhGYg, Ch fhY bSe Edi CTNGUg s
(3BNQgG (B:s
(3hbGd CHheMeO GdOdjd Ydi Cfg GSe GdJfhjf aCfTOfG ced GdcJGH s
(3fSNI KGdKI JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX hGdYHGQGJ hJRjO aj BNQgG UaMJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B27s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B376 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B90 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1800s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdfMhs